Prediction and quantification of bioclogging depth limit and rate based on numerical simulation and experimental validation in managed aquifer recharge. Issue 12 (1st December 2022) - Ye, Xueyan; Ma, Xiaofeng; Du, Xinqiang; Cui, Ruijuan; Wan, Yuyu
Abstract: Many microorganisms are naturally occurring in both recharging water and porous media, and microorganisms will grow and clog the pores of porous media. Porous media show different clogging depth and rate, which depends on the carbon source concentration. The bioclogging depth limit and rate under the effect of the nutrient concentration can be disentangled through column experiments and numerical simulation approaches. We use the TOUGHREACT method‐based on the monod equation of microbial growth to explore the process of microbial growth and permeability change, and correct with experimental results. The experimental results show the influence of nutrient concentration (glucose) on microbial growth and clogging of porous medium, and leads to clogging of porous medium. The clogging rate was defined as the rate of change of hydraulic conductivity with time for quantitative study of bioclogging in our study. Simulated results found that the clogging rate increases 0.035 and 0.00673 (m/d/min) respectively in the glucose concentration range of 0.045–0.6 and 0.6–5 mmol/L, simultaneously, the ultimate clogging depth decreases 18.2 and 1.7 mm respectively in the glucose concentration range of 0.045–0.6 and 0.6–5 mmol/L. The aim of this study was to evaluate the effects of nutrient concentrations on bioclogging and shed light on the establishment of nutrient concentration standards for recharge water during groundwater artificial recharge. Abstract : The influence of glucose concentration on clogging rate and ultimate clogging depth.